1986
DOI: 10.1002/bjs.1800730315
|View full text |Cite
|
Sign up to set email alerts
|

Major amputation compared with graft occlusion as the end point for assessing results of bypass surgery in lower limb ischaemia

Abstract: Cumulative graft patency rates calculated using graft occlusion as the end point are the standard method of presenting results of bypass surgery for lower limb ischaemia. The problems of using graft occlusion as the end point are that this is not easily documented and it gives no indication of the condition of the patient's limb after the graft occludes. The date of amputation is a well defined end point and it means treatment has failed. It is used to calculate cumulative limb salvage rates. Using the two tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Therefore, only 27% of all the patients were still alive with the limb. These rates are similar to those reported by others for populations with similar comorbidities, 2,3,13,23,24 and the mortality rate is similar to those rates in nonoperated populations with similar degrees of peripheral vascular disease. 24 For those patients who do survive, the outlook is not grim.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, only 27% of all the patients were still alive with the limb. These rates are similar to those reported by others for populations with similar comorbidities, 2,3,13,23,24 and the mortality rate is similar to those rates in nonoperated populations with similar degrees of peripheral vascular disease. 24 For those patients who do survive, the outlook is not grim.…”
Section: Discussionsupporting
confidence: 90%
“…2,4 Cigarette smoking and the presence of a relative hypercoagulable state requiring warfarin therapy are documented risk factors for decreased graft patency and progression of arterial occlusive disease. 8,[25][26][27] In a prospective study, Greenhalgh et al 28 demonstrated that elevated blood level of carboxyhemoglobin was associated with arterial graft occlusion. The importance of smoking cessation should be stressed at each patient encounter.…”
Section: Discussionmentioning
confidence: 99%